Vaccination strategies against wild poliomyelitis in polio-free settings: outbreak risk modelling study and cost-effectiveness analysis - Mark Jit; Kaja Abbas; Megan Auzenbergs; Corey M Peak; Arend Voorman; Kathleen M O’Reilly (BMJ Global Health)
The 2021 importation of wild poliovirus serotype 1 (WPV1) into Malawi with subsequent international spread represented the first WPV1 cases in Africa since 2016. Preventing importations and spread of WPV1 is critical and dependent on population immunity provided through routine immunisation (RI) and supplementary immunisation activities (SIAs). We aim to estimate outbreak risk and costs, given the importation of WPV1 for non-endemic countries in the WHO Africa region. We developed a stochastic mathematical model of polio transmission dynamics to evaluate the probability of an outbreak, expected number of poliomyelitis cases, costs and incremental cost-effectiveness ratios under different vaccination strategies. Across variable RI coverage, we explore three key strategies: RI+outbreak SIAs (oSIAs), RI+oSIAs+annual preventative SIAs (pSIAs) and RI+oSIAs+biennial pSIAs. Results are presented in 2023 USD over a 5year- time horizon from the Global Polio Eradication Initiative (GPEI) and health system perspectives. The annual pSIA strategy has the greatest probability of no outbreaks in comparison to other strategies: under our model assumptions, annual pSIAs result in an 80% probability of no outbreaks when RI coverage is ≥50%. The biennial pSIA strategy requires RI coverage ≥65% to achieve an equivalent risk of no outbreaks. The strategy with no pSIAs requires ≥75% RI coverage to achieve an equivalent risk of no outbreaks. For the health system, when RI coverage is between 35% and 60%, both pSIA strategies are cost-saving. For the GPEI, below 65% RI pSIA strategies are cost-effective, but the biennial pSIA strategy incurs higher costs in comparison to annual pSIAs due to more oSIAs required to stop outbreaks. Prioritisation of pSIAs must balance outbreak risk against implementation costs, ideally favouring the smallest manageable outbreak risk compatible with elimination. We infer that there are few short-term risks due to population immunity from RI, but without pSIAs, long-term risks accumulate and can result in outbreaks with the potential for international spread.